EARLY TESTING OF BLOOD SUGAR AS A PREVENTION OF DIABETES MELLETUS - Astik Umiyah (Universitas Borneo Tarakan, 2022)
Diabetes mellitus is a non-communicable disease that poses a serious threat to global and national health.In recent years, Diabetes Mellitus has killed millions of people from various parts of the world with complications that are not treated properly, then the disease can cause complications of other chronic diseases and cause death if not controlled. The purpose of this service is to mobilize public awareness to carry out early examinations as an effort to find out health conditions early and at the same time prevent Diabetes Milletus. The method used is to conduct random blood sugar checks directly to the places of institutions in the pesantren environment with the aim of making it easier for the pesantren community to get health services. This service activity will evaluate activities on a regular basis to be able to control and at the same time monitor the health of managers in Islamic boarding schools. The next step of empowerment is the first step taken in preventing Diabetes Mellitus is by periodically detecting blood sugar by checking blood sugar levels every month. The following steps do exercise, eating arrangements can stabilize blood glucose and improve quality of lifeKeywords: Diabetes mellitus